Analisis Pertumbuhan dan Tingkat Kematangan Gonad Ikan Kembung (Rastrelliger) untuk Mendukung Pengelolaan Perikanan Berkelanjutan - Agnes Juwita Dawolo; Rosevelt Cerdas Lase; Julpin Carles Waruwu; Rosmawati Gea; Sesilia Viktoria Harefa; Seprina Zai (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2025)
Fish growth refers to the growth of body size which includes length and weight, as well as the development of fish body tissues within a certain period of time.Growth does not only occur in a physical sense but also includes biological and physiological changes in the fish body.In an ecological context, fish growth is related to the ability to survive, adapt, and reproduce in an environment with various internal and external factors.The implementation of the practicum of population dynamics and fish stock assessment was carried out in the Nias University building, room 2 of the Faculty of Science and Technology. The morphometric measurements were carried out by measuring the total length, stag length and standard length.The total length was measured from the distance between the tip of the head end and the tip of the caudal fin back.Growth of strange mackerel through the relationship between length and weight using the growth formula expressed in the form of a linear regression equation. The equation obtained from the analysis of measurement data shows the length-weight relationship with the equation Y 2.8771x-1.7473 and R2 value of 0.6688. The coefficient b value of 1.7473 indicates that mackerel has a negative allometric growth pattern, which means weight gain. Mackerel (Rastrelliger sp.) is the main indicator of fish growth and health based on the results of morphometric studies that show variations in length and weight.